DAMPAK PEMBERLAKUAN TARIF IMPOR TERHADAP KINERJA EKONOMI KOMODITAS KEDELAI DAN DISTRIBUSI KESEJAHTERAAN DI INDONESIA - Elok Nurhiasati; Moh. Rifai; Asnah Asnah; Wahyunindyawati Wahyunindyawati (BUANA SAINS, 2010)
Research was aimed at: 1) analyzing the effect of imported soybean tariff policy on demand, supply, price and import of soybean, 2) analyzing import tariff policy of soybean and effects on related economic units’ welfare that covered producer, consumer, and government. Secondary data being used, involving time series of years 1969-2002, analyzed by simultaneous equity system using 2 SLS, continued by analyses of policy simulation and welfare distribution. Import tariff policy produces some effects such as decrease total demand, declined demand for tempe industry, increased demand for tahu industry, decreased demand for ketchup industry, reduced demand for seed, improved supply, decreased farmer level price, inclined wholesale price, increased imported price and descended import. Welfare distribution analysis display that import tariff influences the improvement of producer’s surplus and government’ income but yields in reduced consumers surplus and economic inefficiency of production and consumption. Higher import tariff implicates higher economic inefficiency as shown by higher netto effect value, showing the decrease of total welfare rate. The most suitable import tariff policy connects to 30% because ratio value of producer’s and consumer’s surplus and ratio of government income and consumer’s surplus remain highest compared to other alternatives